Earnings quality: an analysis of Indonesia manufacturing companies with dividend policy as a moderating variable / Maria Stefani Osesoga - Osesoga, Maria Stefani (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study aimed to examine the factors that influenced earnings quality in manufacturing sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Earnings quality is the ability of company-generated profit information to influence the decisions of financial statement users. Earnings information is used as a basis for consideration in making decisions so companies are required to provide quality earnings information. Earnings quality in this study was measured by the Earnings Response Coefficient (ERC). ERC is a measure of the magnitude of the abnormal return of a stock in response to unexpected earnings reported by the company. In this study, the factors that were predicted to affect ERC were profitability, leverage, firm size, and liquidity with dividend policy as a factor that could moderate the relationship with ERC. Based on the results, it can be concluded that profitability, firm size, and liquidity had a significant positive effect on earnings quality (ERC), with dividend policy as a moderating variable. Meanwhile, leverage (DER) had no effect on earnings quality with dividend policy as a moderating variable.